Observability engineering achieving production excellence - Majors, Charity; Fong-Jones, Liz; Miranda, George (O'Reilly Media, Inc., 2022)
Observability is critical for building, changing, and understanding the software that powers complex modern systems. Teams that adopt observability are much better equipped to ship code swiftly and confidently, identify outliers and aberrant behaviors, and understand the experience of each and every user. This practical book explains the value of observable systems and shows you how to practice observability-driven development. Authors Charity Majors, Liz Fong-Jones, and George Miranda from Honeycomb explain what constitutes good observability, show you how to improve upon what you're doing today, and provide practical dos and don'ts for migrating from legacy tooling, such as metrics, monitoring, and log management. You'll also learn the impact observability has on organizational culture (and vice versa).
Includes index
Keywords: Web site development; Computer software -- Development; Computer software -- Testing; Sites Web; Développement; Computer software; Development; Computer software; Testing